Research on proposal of the science and technology solutions to promote the development of agricultural industrialization along Hochiminh road in North Central region - Tuan, Tran Anh; Hang, Truong Thu (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
Agricultural industrialization development is a relatively new concept in our country, but its content is not new and has been implemented in some places with different models. Since the Government decided to invest and to operate Ho Chi Minh road through 06 provinces in the North Central region (Thanh Hoa, Nghe An, Ha Tinh, Quang Binh, Quang Tri, Thua Thien Hue), it has created large production areas along the corridor, especially, there are many enterprises such as Lam Son Sugar Joint Stock Company, TH Milk Joint Stock Company; Nafoods Group Joint Stock Company,... pioneering investment in a methodical manner, developing value chains and is seen as models of industrial development and has been successful in production and business, spreading and attacting people to join. This is also a region with great potential for large land and forest land areas, concentrating on National parks and Nature reserves,... which is suitable for industrial development and sustainable development. Code: 18081601